ASSESSMENT OF THE EFFECTIVENESS OF FLOODING OF RESORT-TYPE OIL DEPOSITS - Ibotov Oybek Kuyliyevich; Azizova Dilorom Gayratovna; Ashurov Murodulla Kholbayevich (American Journals Publishing, 2023)
However, when flooding fields with hard-to-recover reserves (high oil viscosity, low permeability and large heterogeneity of formations), oil recovery factors decrease to 0.3-0.35 with increasing flushing ratio from 0.8-1 to 5-7, and with viscosity oil more than 25-30 mPa s, waterflooding often becomes ineffective.